The 3-year follow-up of a fully biodegradable implantable device closure for perimembranous ventricular septal defects in children using echocardiography - Cong, Juan; Cui, Cunying; Huang, Danqing; Wang, Ying; Liu, Sifan; Song, Shubo; Fan, Taibing (Frontiers in Cardiovascular Medicine, 2024)
Objects To investigate the morphologic changes of a novel fully biodegradable implantable device after closing perimembranous ventricular septal defect (Pm-VSD) and to evaluate the effect of the occluder on the myocardial function in the patients in a three-year follow-up period.Methods A total of thirty Pm-VSD patients with successful closure by the fully biodegradable occluder was performed 1-year, 2-year and 3-year follow-up after implantation, respectively. 30 matched health children were enrolled as control subjects. At discharge and every follow-up visit, the lengths of left and right discs of the novel device were measured in the apical three-and four-chamber as well as short-axis view. At the end of follow-up, using three-dimensional speckle-tracking condition, the values of myocardial deformation, including global longitudinal strain, global circumferential strain and global area strain, were acquired.The fully bioabsorbable double-disk occluder gradually decreased over time and were invisible finally under echocardiographic scanning during the follow-up (P<0.05). At the end of the third year, the myocardial deformation parameters were no significant difference between the cases implanted the novel devices and the normal controls, but also between the basal segments of the ventricle septa and of LV free wall among the subjects who completed the Pm-VSD closure using the fully biodegradable occluder (P>0.05).The novel fully biodegradable occluder is a safe, effective and perfect alternative for VSD treatment. Echocardiography plays a crucial role in the follow-up of the new type of occluder implantation.